Scarlette Beane - Wallace, Karen; Berkeley, Jon. (New York : Dial Books for Young Readers, 1999)
When family members give five-year-old Scarlette a garden, she succeeds in growing gigantic vegetables and creating something wonderful.
Keywords: Gardening -- Fiction; Vegetables -- Fiction